2006
DOI: 10.1007/s00134-006-0360-x
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure in septic shock: predictive value of Doppler-based renal arterial resistive index

Abstract: Doppler-based determination of RI on D1 in septic shock patients may help identify those who will develop ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
153
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(170 citation statements)
references
References 27 publications
12
153
0
5
Order By: Relevance
“…We did not assess the use of the lowest SCr level during admission for estimating baseline kidney function, as performed in other studies (5,11,22). This method of estimating baseline SCr is an alternative for use in retrospective studies, whereas we sought to evaluate methods of classifying patients by pRIFLE criteria prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess the use of the lowest SCr level during admission for estimating baseline kidney function, as performed in other studies (5,11,22). This method of estimating baseline SCr is an alternative for use in retrospective studies, whereas we sought to evaluate methods of classifying patients by pRIFLE criteria prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lerolle et al [29] showed that patients who developed renal dysfunction exhibited on the admission higher RRI values than those who did not develop it (0.77 vs 0.68, respectively, P \ 0.001). A RRI[0.74 at inclusion had a sensitivity of 78 % (95 % CI 52-94 %), a specificity of 77 % (95 % CI 50-93 %) for severe renal dysfunction (Class I or F according to RIFLE classification).…”
Section: Rri and Akimentioning
confidence: 99%
“…25 A threshold of RI has been proposed to detect the risk of acute kidney injury 29 and may help to adjust therapeutic modalities for perfusion at the bedside. 30 The RBF increase during infusion of a "renal dopamine dose" at day 6 is associated with vasodilatation reflected by RI decrease.…”
Section: Discussionmentioning
confidence: 99%